TEACHING COMBINED WITH ENVIRONMENTAL PRESERVATION: DIGITAL EDUCATIONAL PRODUCTS ON THE IMPORTANCE OF THE MICROBIOTA OF THE CERRADO BIOME - Gonà§alves, Tatiane; Moura , Jadson (CIPEEX, 2022)
THE CERRADO BIOME IS THE SECOND LARGEST ECOSYSTEM IN BRAZIL, HAS THOUSANDS OF ANIMAL AND PLANT SPECIES, IN ADDITION TO A RICH MICROBIOTA, BEING CONSIDERED ONE OF THE HOTSPOTS OF BIOLOGICAL WEALTH WORLDWIDE, THAT IS, IT HAS A HIGH RATE OF ENDEMIC LIVING BEINGS. THE ENTIRE WEALTH OF THE BIOME IS UNDER CONSTANT THREAT DUE TO HIGH RATES OF DEFORESTATION, RESULTING FROM THE EXPANSION OF THE AGRICULTURAL FRONTIER. SEVERAL STUDIES POINT TO THE HIGH BIOTECHNOLOGICAL POTENTIAL OF THE CERRADO, IN ADDITION TO ITS IMPORTANCE FOR THE MAINTENANCE OF WATER CYCLES AND ECOLOGICAL RELATIONSHIPS IN THE COUNTRY. AWARENESS THROUGH ENVIRONMENTAL EDUCATION (EE) IS ESSENTIAL FOR THE PROTECTION OF THIS ECOSYSTEM. THIS WORK PROPOSES TO PRODUCE TWO DIGITAL EE DIDACTIC TOOLS, A BOOKLET AND AN INTERACTIVE QUIZ, TO BE APPLIED TO HIGH SCHOOL STUDENTS IN ITAPACI, GOIS. THE OBJECTIVE IS TO DEMONSTRATE THE IMPORTANCE OF THE CERRADO MICROBIOTA, AND THE ROLE OF CITIZENS IN PROTECTING BIOLOGICAL HERITAGE. INFORMATIVE LECTURES AND STUDY OF THE MATERIAL WILL BE HELD, PRODUCED THROUGH A CAREFUL BIBLIOGRAPHIC REVIEW, AND WRITTEN IN AN ACCESSIBLE LANGUAGE, LATER A DIGITAL FIXATION GAME WILL BE APPLIED, AND BOTH TOOLS SEEK TO DIALOGUE WITH THE REALITY WHERE STUDENTS OF THE GENERATION CALLED ''DIGITAL NATIVES''. IT IS EXPECTED AT THE END OF THE STUDY THAT THE TOOLS WILL BE EFFECTIVE IN PROMOTING EE AND FORMING A CRITICAL CONSCIENCE, ENCOURAGING PARTICIPATION IN ENVIRONMENTAL PROTECTION PROJECTS, EXERCISING FULL CITIZENSHIP OF THE STUDENTS.